Developing a Radiomics Signature for Supratentorial Extra-Ventricular Ependymoma Using Multimodal MR Imaging - Safai, Apoorva; Shinde, Sumeet; Jadhav, Manali; Chougule, Tanay; Indoria, Abhilasha; Kumar, Manoj; Santosh, Vani; Jabeen, Shumyla; Beniwal, Manish; Konar, Subhash; Saini, Jitender; Ingalhalikar, Madhura (Frontiers in Neurology, 2021)
Rationale and Objectives: To build a machine learning-based diagnostic model that can accurately distinguish adult Supratentorial Extraventricular Ependymoma (STEE) from similarly appearing high-grade gliomas (HGG) using quantitative radiomic signatures from a multi-parametric MRI framework. Materials and Methods: We computed radiomic features on the preprocessed and segmented tumor masks from a pre-operative multi-parametric MRI dataset (Contrast Enhanced T1 (T1ce), T2, Fluid Attenuated Inversion Recovery (FLAIR), Apparent Diffusion Coefficient (ADC)) from STEE (n=15), HGG-Grade IV (HGG-G4) (n=24) and HGG-Grade III (HGG-G3) (n=36)) patients, followed by an optimum two-stage feature selection and multiclass classification. Performance of multiple classifiers was evaluated on both unimodal and multimodal feature sets and most discriminative radiomic features involved in the classification of STEE from HGG subtypes were obtained. Results: Multimodal features demonstrated higher classification performance over the unimodal feature set in discriminating STEE and HGG subtypes with an accuracy of 68% on test data and above 80% on cross-validation, along with an overall above 90% specificity. Among unimodal feature sets, those extracted from FLAIR demonstrated high classification performance in delineating all three tumor groups. Texture-based radiomic features particularly from FLAIR were most important in discriminating STEE from HGG-G4, whereas first-order features from T2 and ADC consistently ranked higher in differentiating multiple tumor groups. Conclusions: This study illustrates the utility of radiomics based multimodal MRI framework in accurately discriminating similarly appearing adult STEE from HGG subtypes. Radiomic features from multiple MRI modalities could capture intricate and complementary information for a robust and highly accurate multiclass tumor classification.